Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/1440-1630.12833
|View full text |Cite
|
Sign up to set email alerts
|

The impact of face‐to‐face mental health consumer‐led teaching on occupational therapy student empathy levels: Two group comparison design

Abstract: Introduction: Australian and New Zealand accreditation standards for occupational therapy courses mandate consumer involvement in the design, delivery, and evaluation of courses. Consumer involvement in medical, dental, and nursing education has been evidenced as a factor for increasing student empathy. To date, there has been no known research on the impact of mental health consumer involvement on occupational therapy students' empathy. The aim of this study was to investigate if occupational therapy students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The involvement of people with lived and living experience in the education and ongoing professional development of health professionals, and as means of improving health outcomes is not a new phenomenon. The importance and value of involving people with lived and living experience of mental health issues has received global recognition as an approach to improving service development and delivery [1] and enhancing the education of health students and professionals [2][3][4][5]. This increased emphasis has been partly in response to the mandatory requirement of some professional bodies that people with lived experience, or consumers, be involved in the design, delivery, and evaluation of the education of health professionals (see for example: [6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of people with lived and living experience in the education and ongoing professional development of health professionals, and as means of improving health outcomes is not a new phenomenon. The importance and value of involving people with lived and living experience of mental health issues has received global recognition as an approach to improving service development and delivery [1] and enhancing the education of health students and professionals [2][3][4][5]. This increased emphasis has been partly in response to the mandatory requirement of some professional bodies that people with lived experience, or consumers, be involved in the design, delivery, and evaluation of the education of health professionals (see for example: [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Educators have a pivotal role to play in building capacity by providing health students and staff with opportunities to participate in learning activities that include engagement with people with lived experience. Specifically considering preparation to work in mental health practice, meaningful involvement of people with lived experience in the design and delivery of education can assist students to develop skills in critical thinking, communication and empathy, as well as challenge stereotypes, and address stigma and fear [2][3][4][5]. Opportunities to learn from and with people with lived experience are critical to develop future health professionals with the capability to work collaboratively and compassionately with people experiencing psychological distress or mental ill-health, their families and carers [11][12][13], and who can contribute to the development of a responsive, person-centred, and humane mental health system [14].…”
Section: Introductionmentioning
confidence: 99%
“…The papers also reflect a range of levels of consumer involvement from consulting to collaboration, with many of the publications being co‐authored with consumer investigators. Four papers focus on occupational therapy education, with three discussing the involvement of lived experience experts in mental health (Happel et al, 2022; Logan et al, 2022; Scanlan et al, 2022) and one discussing consumers providing feedback to students during practice placements (Bevitt et al, 2022). Two focus on the involvement of consumers in developing services (Harris et al, 2022; Pozniak et al, 2022), and three focus on consumer partnerships in research (Chapman et al, 2022; Cox et al, 2022; Liddle et al, 2022).…”
mentioning
confidence: 99%
“…Students also reported that they improved clinical skills and indicated that stigma could be reduced by seeing the strength and resilience of consumer educators. Logan et al's (2022) paper, like Scanlan et al's, sought to demonstrate the impact of consumer educators delivering co‐designed curriculum. The quasi‐experimental study indicated that student's empathy was high in both the consumer‐led teaching and the control group, both prior to and after teaching with no significant differences between groups after teaching.…”
mentioning
confidence: 99%